An Adaptive and Sustained Landslide Monitoring and Early Warning System - Fathani, Teuku Faisal (Springer, 2014)
Areas prone to mass movement are widespread in Indonesia. The potential for landslide disasters in several regions is controlled by the geotechnical and geological conditions and triggered by high intensity rainfall and/or earthquake activity. The vulnerability to landslides is made worse by intensive land-use development. The urgent issues to be addressed are the dense populations residing in areas prone to mass movement and the failure to relocate the local people to safer areas for socio-economic reasons. Therefore, landslide monitoring, prediction, and early warning systems are urgently required to guarantee the safety of communities living in such areas. A long running and sustainable community-based landslide monitoring and early warning system (EWS) has been developed in Indonesia, with establishment of collaboration among the local government, universities, private sectors, NGOs, and the disaster management community. The main purpose of the program is to establish a strategic approach for disaster risk reduction through the implementation of information flow (for warning levels) and order/command systems (for evacuation). These activities have already met the community needs, helped save lives, and continued to obtain solid community support. In order to extend the effort, further challenges are to expand the project coverage, and propose more effective landslide monitoring, early warning, analysis, and visualization. In addition, the capabilities in socioeconomic risk assessment need to be expedited to help identify those most at risk within the community. This paper describes the achievements and the current activities of the IPL Project (IPL-158) “Development of Community-based Landslide Early Warning System”.